ASSESSMENT OF THE PATTERN AND PATRONAGE OF RESTAURANTS/EATERIES IN ILORIN EAST LOCAL GOVERNMENT AREA OF KWARA STATE, NIGERIA - Malik, N.A. (FUDMA Journal of Earth and Environmental Sciences, 2024)
This paper examines the respondent's ratings of the quality of food, environment, services rendered by staff, types of customers that visit the restaurant, and their socio-economic status. The sample frame was the 28 selected restaurants, while five respondents were randomly selected from each restaurant to get a sample size of 140 respondents. The data generated were analyzed through the Arc-GIS tool, percentages, and graphs. The study revealed that 39.3% of the respondents earned below N30,000, while 12.9% earned above N90,000. Varieties of food were sold in the restaurants comprising Nigerian dishes (46.4%), local dishes/ Yoruba, 25%, International dishes, 17.9%, and Nigerian and International dishes, 10.7%. The level of patronage shows that 35.1% of the modern restaurants had between 21 and 30 customers daily, while 43% of the traditional restaurants had between 31 and 40 customers daily. The major customers of the restaurants were 46% (working class), 29% students, and 13% locals. The rating by respondents on the quality of food, restaurant environment, service rendered by staff, and level of customer satisfaction showed that 58.6%, 67.9%, and 89.3% rated them as excellent, very good, and sound, respectively. The distributional pattern of the restaurants showed that they are clustered together along major roads. This pattern may be attributed to the fact that restaurants prefer locations that are easily accessible to their customers. The study concluded that the various indices of customer assessment should be maintained and improved upon by the operators of restaurants in the study area.